(untitled) - FAO (Rome, 1997)
This report is ostensibly about land quality indicators ( LQIs ). However, anyone who reads it will find a useful complation of advice, experience and opinion on why land quality information is important for sustainable development and how it can be used more effectively for planning and decision making. But the report also poses as many questions as it answers, which in itself reflects the diversity of viewpoints on indicators.
Keywords: natural resources